2000
DOI: 10.2337/diacare.23.10.1516
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of childhood type 1 diabetes worldwide. Diabetes Mondiale (DiaMond) Project Group.

Abstract: OBJECTIVE: To investigate and monitor the patterns in incidence of childhood type 1 diabetes worldwide. RESEARCH DESIGN AND METHODS: The incidence of type 1 diabetes (per 100,000 per year) from 1990 to 1994 was determined in children < or =14 years of age from 100 centers in 50 countries. A total of 19,164 cases were diagnosed in study populations totaling 75.1 million children. The annual incidence rates were calculated per 100,000 population. RESULTS: The overall age-adjusted incidence of type 1 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
445
6
32

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 869 publications
(499 citation statements)
references
References 17 publications
16
445
6
32
Order By: Relevance
“…A potential problem with this study is the completeness of ascertainment, which was lower than in the childhood studies [4,6,7]. This is a reflection of the difficulties encountered when trying to ascertain young adults, who are less visible in the health care system, while diabetes in this age group is more heterogeneous and classification more complex.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A potential problem with this study is the completeness of ascertainment, which was lower than in the childhood studies [4,6,7]. This is a reflection of the difficulties encountered when trying to ascertain young adults, who are less visible in the health care system, while diabetes in this age group is more heterogeneous and classification more complex.…”
Section: Discussionmentioning
confidence: 92%
“…The incidence of Type 1 diabetes in children varies more than tenfold across Europe and 350-fold between Finland and China [4,7]. We selected study areas with a childhood incidence ranging from 5.3 per 100000 person years (Bucharest) to 41.6 per 100000 person years (Sardinia), and showed that there is far less variation in incidence in young adults from the same regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence was greatest among children of 10-14 years of age at onset (Table 1), as in most populations studied worldwide [21]. The increase in Japan was mainly due to a rapid increase in the number of children aged 10-14 years, in contrast to countries with populations of Caucasoid origin (Fig.…”
Section: Childhood Type 1 Diabetesmentioning
confidence: 86%
“…While increasing rates of obesity and sedentary lifestyles appear to account for the increase in type 2 diabetes, relatively little is known about why type 1 diabetes is increasing. Since the earliest registers of type 1 diabetes, it has been evident that a large (at least 35-fold) geographical difference in incidence exists, which has persisted until today [3]. Although these differences are considered to result from varying distributions of genetic and environmental risk factors, the exact variations and contributions of these risk factors remain unknown.…”
Section: Introductionmentioning
confidence: 99%